آفاق تعزيز اندماج الجزائر في سلاسل القيمة العالمية عبر سلاسل القيمة الإقليمية فرص وتحديات النشاط ضمن منطقة التجارة الحرة القارية الإفريقية (AFCFTA): Promoting Algeria’s integration into global value chains through regional value chains- Opportunities and challenges for activity in (AFCFTA) - نادية تاهمي; نادية براهيمي (Journal of North African Economies, 2025)
In our research, we address the issue of enhancing Algeria's positive participation in global value chains through the regional chains expected to be formed within the AfCFTA area, within the framework of economic integration relations and value chain building. We aim to explore the opportunities available for Algeria's activity in this region, which has been based on exporting energy and oil resources as raw materials for decades, making this participation ineffective. This led the Algerian government since 2020 to adopt a program based on a strategy to diversify exports outside the hydrocarbon sector. By applying the exploratory descriptive case study approach, and the network survey of various research, studies, and reports prepared by specialized international organizations, we reached the most important results: the existence of 03 value chains among 94 promising and possible value chains at the continental level, Algeria can participate in them, within its activity in the AfCFTA area, and achieve its developmental goals under the adopted economic recovery program.